2014
DOI: 10.22146/ijg.6078
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Jos City Road Network, Nigeria

Abstract: ἀe performance of road network depends on its topological characteristics which help to deḀne its connectiv-ity. ἀis paper analyses the topological characteristic of Jos city road network and its bearing on traᴀc ᰀow situations. Simple graph theoretic measures oᬀered the framework on which the problem was approached. ἀe study requires the abstraction and analysis of the topological structure by selection of certain variables relating to the road connectivity. ἀese include the Beta, Gamma and Alpha index, the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In another development, Oluwole (2014) observed that in Kaduna the various ethnic and religious groups have influence in the pattern of residential mobility. He said some parts of the metropolis are dominated by certain ethnic and/or religious groups.…”
Section: The Pattern Of Residential Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In another development, Oluwole (2014) observed that in Kaduna the various ethnic and religious groups have influence in the pattern of residential mobility. He said some parts of the metropolis are dominated by certain ethnic and/or religious groups.…”
Section: The Pattern Of Residential Mobilitymentioning
confidence: 99%
“…Numerous studies according to Oluwole (2014) have shown that the propensity to move is associated with a number of factors such as age, stage in one's life cycle, socio-economic factors, housing tenure, duration of residence, cost of rent and location relative to the city centre. Other factors include environmental consideration of the area, actors' involvement in the search process and the tendency of households to maximise the expected utility (Olatubara, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…He found that dynamics of spatial structure contribute to changes in resident mobility. Another study conducted by Oluwole & Daful (2014) in Nigeria found that a city's road network achieved an average level of connectivity.…”
Section: Improvement In Existing Roadsmentioning
confidence: 99%
“…Road network performance depends on topological characteristics that help determine the road connectivity (Oluwole and Daful, 2014). The level of accessibility can be measured using an alpha (α) and beta index (β).…”
mentioning
confidence: 99%